Islamization of Knowledge of Ismail Raji Faruqi: Integration-Interconnection to the Contextualization of Indonesian Science - Syihabuddin, Muhammad; Manggala, Kayan; Mustofa, M. Lutfi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This article discusses the concept of Islamization of knowledge promoted by Ismail Raji Faruqi. This concept aims to defeat secularism that blinds Muslims and brings misfortune. The spread of secularism has encouraged Muslims to make concessions to what the West offers them. Therefore, reading the Islamization of knowledge in the context of scientific integration-interconnection becomes essential to raise awareness among Muslims who are considered to glorify secular science so that people are too far from the concept of tawhid (monotheism). This research used a literature review method through several textual sources related to the topic discussed, primarily Faruqi's work entitled